Capital social y desarrollo comunitarío: caso de las juntas de usuarios del sistema de riego del valle del Daule - Jiménez García, Katherine Elizabeth (2009)
This study presents the different theories that have been proposed around the capital as well as to determine whether the Members of the Valle del Daule present empirical evidence to support the existing literature. For this propose was made a questionnaire that was developed by the Centro de Investigations Rurales de la ESPOL, and it is based on the questionnaire that is proposed by the World Bank. The questionnaire is looking for determining the existence of social capital and, tries to measure it. The research was conducted for members of América Lomas, Higuerón, El Mate and San Jacinto. As tools for determining the existence of social capital and the factors that influence its development, using tools such as factor analysis, cluster analysis in addition to using descriptive statistics which will be used to explore the main characteristics of the data. The conclusion was the factors that influence social capital in this area are: trust, networks, cooperation. In addition it was determined difference in social capital between the users when there is a segmentation of the database by incomes, extension of the land.